Accessing targeted therapies for cancer: self and collective advocacy alongside and beyond mainstream cancer charities. Issue 1 (2nd January 2021) - Kerr, Anne; Chekar, Choon Key; Swallow, Julia; Ross, Emily; Cunningham-Burley, Sarah
Abstract : As precision oncology has evolved, patients and their families have become more involved in efforts to access these treatments via fundraising and campaigning that take place outside of the larger cancer charities. In this paper, we explore the solidarities, networks, and emotional work of the UK-based access advocates, drawing on the stories of nine advocates, which included interviews and content analyses of their social media posts and coverage of their case in news, commentary, and fundraising websites. We consider the emotional and knowledge work of building networks that spanned consumerist and activist agendas, forged individual and collective goals, and orientations toward the public, private, and third sectors as part of securing support and access. Through these various practices, the actors we have studied cultivated personal advantage and solidarities with other patients and advocates, and in so doing engaged in self and collective advocacy alongside and beyond mainstream cancer charities.